CLINICAL PROFILE AND OUTCOME OF NEONATES ADMITTED TO A SECONDARY-LEVEL NEONATAL INTENSIVE CARE UNIT IN NORTH INDIA - Yousuf, Shagufta; Tali, Showkat Hussain; Hussain, Iftikhar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: The objective of this study was to evaluate the performance of a secondary-level neonatal intensive care unit (NICU). Methods: A total of 336 neonates were enrolled in the study. Their clinical profiles at admission and final outcomes were recorded in a predesigned pro forma. Results: Hyperbilirubinemia, sepsis, and perinatal asphyxia were the most common reasons for admission. Eighty-five percentage of the neonates could be managed in secondary-level newborn unit with comparable mortality and mortality to a tertiary-level newborn care unit. Conclusion: Strengthening of secondary newborn care units is a viable option that will help to decrease the burden of tertiary-level NICUs.